Wilfrid Sellars. - Rosenberg, Jay F. (OUP Oxford, 2007)
Wilfrid Sellars was and remains one of the most prominent and important twentieth-century philosophers. Jay Rosenberg brings together his previously published studies of the central elements and implications of Sellars' philosophy, along with three new essays that further highlight and articulate the significance of his work.